Systematic approaches for design of ionic liquids and their mixtures for enhanced carbon capture purpose - Chong, Fah Keen (2017)
Post-combustion capture using amine-based solvents has been considered as the most viable technology for carbon capture, to mitigate industrial carbon dioxide (CO2) emissions; but the solvents show a number of shortcomings. Recently, ionic liquids (ILs) are suggested as possible alternative to amine-based solvents, for they can be molecularly engineered to match various target thermophysical properties. This work focused on the development of systematic approaches to design IL-based solvents for carbon capture purpose. The first focus of this work is to develop an insight-based based visual approach to determine potential IL solvents as substitute to conventional carbon capture solvents. This approach allows visualisation of high-dimensional problem to be visualised in two or three dimensions, and assist designers without mathematical programming background in IL design. Following that, a mathematical optimisation approach to design optimal IL solvent for CO2 capture purpose was developed as second focus of this thesis. This has been done by formulating the IL solvent design problem as mixed integer non-linear programming (MINLP) optimisation problem. The abovementioned approaches were developed to design task-specific ILs with high CO2 absorption capacity as substitute to common carbon capture solvents. However, studies show that such ILs are relatively more expensive and have higher viscosities. To reduce the cost and viscosity of solvent, task-specific IL can be mixed with conventional IL, ensuring CO2 solubility remains high, while viscosity and cost are acceptable. Hence, the previously developed visual approach was extended to design pure ILs and IL mixtures, specifically to capture CO2.